(9x-7)=(7x+1)

Simple and best practice solution for (9x-7)=(7x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (9x-7)=(7x+1) equation:



(9x-7)=(7x+1)
We move all terms to the left:
(9x-7)-((7x+1))=0
We get rid of parentheses
9x-((7x+1))-7=0
We calculate terms in parentheses: -((7x+1)), so:
(7x+1)
We get rid of parentheses
7x+1
Back to the equation:
-(7x+1)
We get rid of parentheses
9x-7x-1-7=0
We add all the numbers together, and all the variables
2x-8=0
We move all terms containing x to the left, all other terms to the right
2x=8
x=8/2
x=4

See similar equations:

| 165=(1/2)15h | | 20=150=x×3 | | 54+5x=180 | | -182x=-4 | | 12=(3/4)n | | 4y+16-2y=42-y | | 5x^2-33x-150=0 | | 2x+10+5x=3x+(x+5)+4x | | 2/2c+23=38 | | (x+1)^2-5=20 | | 3(r-4)-14=2(r-7)+7 | | -2(4-x)=x+3(x-2) | | 4x+x-4x=40 | | 20=166x | | m+14.2=-2.41 | | -2x+57=180 | | 3x+x+9=3x+16 | | 5.x/3-3=-7 | | 57-2x=180 | | 6(2x+1)=3(x+8) | | 3(2x-1)=0.5(x+6) | | 4x+5=11+3x | | 5x–18=7 | | 8x^2+8x=424 | | 11m=8m-6 | | -45x-20=20x-12 | | 14x+6-5x=34+5x+19 | | x*5-24=31 | | 10(3.14)*360/10(3.14)=x | | 9/11=x/661 | | -2y-4=2 | | 6(x-3)-2-(x+4)=2 |

Equations solver categories